Fuel Consumption in an Organic Fertilizer Processing Machine - Asbanu, Husen; Chan, Yefri; Esye, Yendi; Faturachman, Danny; Rahardja, Istianto Budhi (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
The demand for organic fertilizer is crucial for small-scale farming businesses, particularly when compared to chemical fertilizers, which are expensive and negatively affect long-term soil fertility. This study aims to determine the specific fuel consumption requirements for gasoline engines used in organic fertilizer processing machines based on the workload applied to the engine. The research compares the actual specific fuel consumption and fuel consumption times for three types of gasoline, RON 90, RON 92, and RON 98, under an engine operating load of 3 kg. The results show that for a 3 kg load, the specific fuel consumption is 10 milliliters for RON 90, 35 milliliters for RON 90, and 25 milliliters for RON 92. The time savings for operating under a 3 kg load are 2.91 minutes with RON 90, 1.99 minutes with RON 92, and the lowest time savings of 0.92 minutes with RON 98.